Implementasi Konsep Seed Pada Interior Bandar Udara Notohadinegoro Jember - Celine Destiana Siem (Intra, 2014)
Jember’s Notohadinegoro Airport is an airport located in Ajung subdistrict, Jember, East Java. The airport has not been opened and the general aviation terminal building condition does not meet the standard as the Airport Terminal. Total capacity of the airport visitors based on real data obtained from interviewing relevant parties. Was done in order to redesign the airport terminal airport terminal building standards appropriate objectives and targets as well as having a design that meets the economic value, social, political and tourism, as well as increasing the potential value of local culture and the city of Jember. The first stage of the redesign is done with the data collection and field observations to find the needs and problems of the object to be in redesigning, then the data is collected and analyzed, problem-solving solutions are then developed into a design concept that is good and right. Interior Redesign uses the concept of natural service "Seed" and the image of the local culture to improve the standard of facilities Jember interior. Local application of culture using the tobacco leaf. Tobacco leaf formation will be applied to the space and also the formation of decorative interior elements. Atmosphere of the room here has a Natural Natural atmosphere in which the application of the Natural materials such as wood and stone on walls, ceilings, and floors, notching design on furniture that suits the design concepts and the use of natural color. The airport in redesigning the better the service, the facilities, the circulation is directed, and informative.